Assessment of Agricultural technology development and transfer in St. Kitts and Nevis - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The Federation of St. Kitts and Nevis is bent on developing agriculture to boost its economy. This goal presents a stimulating challenge to the institutional technology development and transfer system for modernizing the sector and spurring its diversification. The Technology Development and Transfer Structure (TDTS) must aim particularly at increasing productivity to compensate for the smallness of the land area while improving efficiency in the use of water to compensate for the dryness of the climate. Enlightened technology policy, streamlined functional organization of the structures dealing with technology development and transfer and upgraded managerial capability of the relevant professionals, especially in research/development and extension, must be key objectives of the Department of Agriculture as core TDTS institution in each island. As the institutional composition of the local Agricultural TDTS differs between the two islands, these will be trated separately for practical purposes. Contents: Technology Development and Transfer Structure, Basic Institutional Constrains, General recommendations for St Kitts and Nevis, and Specific Proposals